Optimization of hydrolysis conditions for nanocrystal cellulose (CNXL) fabrication / Noorfazila Amin - Amin, Noorfazila (2008)
This study describes an acid hydrolysis technique with subsequent ultrasonification time to produce nanocrystal cellulose (CNXL) from microcrystalline cellulose (MCC). The microcrystalline cellulose was hydrolyzed at difference conditions. The concentration of 40%, 50% and 55% of sulphuric acid were used. Hydrolysis was done at room temperature and 50° C for 30 minutes, 60 minutes and 90 minutes. The colloidal suspension of nanocrystal cellulose produced undergoes centrifugation, followed by filtration, ultasonication and drying in vacuum oven. The nanocrystal cellulose produced was characterized using SEM and Polarized Light Microscope. Difference in hydrolysis conditions affected the size distribution of nanocrystal cellulose produced. The range size distribution of the nanocrytal produced was wide between 85nm-333nm.